Pembelajaran Dari Rumah Dalam Perspektif Wali Murid Sekolah Dasar di Daerah Pedesaan - Daeng Pawero, Abdul Muis; A’an Yusuf Khunaifi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The Learning From Home (BDR) policy aims to cover all levels of education, from kindergarten to college. BDR activities were initially carried out to prevent the spread of Covid-19 in the field of education. In Learning From Home Activities, parents are involved in participating in the learning process, assisting teachers in carrying out the learning process. This research uses a descriptive qualitative method, namely a research method by objectively describing the object to be studied by the author without providing additions or changes to the data obtained in the field. In addition, the credibility of the data source is maintained by its extensin. The collection of research data was carried out by means of observation, interviews and documentation. Based on the findings, Learning from home based on the perspective of parents of elementary school students in Bolaang Mongondow Timur that is; 1) The enthusiasm of the parents of students is caused by the activeness of teachers who proactively establish communication and coordination with the parents of students, 2) Most parents do not use technology facilities in learning from home due to various complex obstacles, such as network access constraints and the absence of smartphone facilities 3) Guardians from the lower middle class who work as farmers and fishermen, have a high level of enthusiasm in learning from home compared to parents from the upper middle class who work as government employees and entrepreneurs. 4) There are parents from the lower middle class who work as farmers and fishermen who prefer to invite their children to help parents in the rice fields or in the sea if they have difficulty in helping teachers when teaching their children about learning at school